2002
DOI: 10.3998/ark.5550190.0003.908
|View full text |Cite
|
Sign up to set email alerts
|

Influence of ring size on the reduction of vinylogous urethanes. Applications to the synthesis of lupinine and epilupinin

Abstract: Short syntheses of the quinolizidine alkaloids lupinine and epilupinine via alkyl 3-(2-thioxo-1-piperdinyl)propanoates and the vinylogous urethanes prepared from them are reported. Alkyl piperidin-2-ylideneacetates were found to undergo reduction of the C=C bond with lithium aluminium hydride more readily than their pyrrolidin-2-ylideneacetate analogues, a finding that is in line with reports of the relative reactivities of double bonds exocyclic to five-and sixmembered rings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The stereochemistry of products 5a–5e, 5g–5h, and 5j–5k was assigned by NOESY experiments (ESI † ) or by comparison with literature NMR values (5f (ref. 46 ) and 5i (ref. 47 )).…”
Section: Resultsmentioning
confidence: 99%
“…The stereochemistry of products 5a–5e, 5g–5h, and 5j–5k was assigned by NOESY experiments (ESI † ) or by comparison with literature NMR values (5f (ref. 46 ) and 5i (ref. 47 )).…”
Section: Resultsmentioning
confidence: 99%
“…With two of the putative target's stereogenic centres in place, the next objective was to introduce the remaining two by a stereoselective reduction of the carbon-carbon double bond of the enaminone unit, a task for which we had established ample precedent in a variety of previous syntheses. 12,18,22, 24 Our experience has been that steric factors favour the preferential delivery of hydride reductants to the bridgehead position C-8a on the face of the double bond anti to the substituent at C-5 (the re face in this case); isomeric mixtures may be formed at C-8, but base-mediated epimerisation facilitates conversion into the isomer containing the equatorial C-8 substituent. Catalytic hydrogenation also occurs on the face of the double bond opposite to the C-5 substituent, with the expected cisstereocontrol at both C-8 and C-8a.…”
Section: Resultsmentioning
confidence: 99%
“…18a: R f 0. 227 (4), 210 (8), 184 (4), 141 (12), 140 (100), 98 (11), 86 (8) and 57 (9 (11), 220 (9), 178 (16), 176 (50), 140 (10), 116 (24), 72 (100) and 57 (31) (found: M + , 319.1913. C 16 H 30 ClNO 3 requires 319.1914).…”
Section: Tert-butyl (−)-(2r3r)-3-(2-oxopyrrolidin-1-yl)-2ethylhexanoa...mentioning
confidence: 95%
See 1 more Smart Citation
“…Removal of the N-Boc protecting group and cyclisation afforded the 8-methyleneindolizidine 319, hydroboration-oxidation of which yielded a 7 : 3 mixture of the diastereomers 314 and 315. The method was also used for the synthesis of the analogous pyrrolizidine alkaloids.A rather old synthesis of lupinine 320 via a vinylogous urethane intermediate 125 has been reinvestigated by Michael and co-workers, who have resolved certain ambiguities in the original work 126. It was found that the vinylogous urethane unit in the intermediate 321, prepared as shown in Scheme 31, was more susceptible to conjugate reduction with lithium aluminium hydride than the corresponding functional group in the fivemembered analogues of 321.…”
mentioning
confidence: 99%